2014
DOI: 10.2298/vsp130714034d
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behavior of children in relation to oral health

Abstract: Most respondents stated that they began to brush their teeth at the age of 4, while a smaller number linked beginning of tooth brushing to the start of school. The parents more often help the boys during tooth brushing. A total of 54.9% of children brush their teeth after every meal, while 40.1% of them brush teeth only once during the day. Twelve year olds brush their teeth more often, especially after a meal. A total of 92.5% of children had never used fluoride tablets nor are the tablets recommended to them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
2
8
0
3
Order By: Relevance
“…As the caries rate is high, oral health knowledge and oral hygiene practices are unsatisfactory, and the use of fluoride is infrequent in China, the present study confirmed that pit and fissure sealants should be promoted strongly as an effective preventive approach for caries among community‐ or school‐based programs. Similar conditions regarding knowledge, oral hygiene practices, and attitude of school children in relation to oral health in neighboring countries, such as India, Serbia, and Iran, were observed . Thus, the results of the present study can provide useful baseline data for developing countries with similar conditions to create their own comprehensive preventive programs.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As the caries rate is high, oral health knowledge and oral hygiene practices are unsatisfactory, and the use of fluoride is infrequent in China, the present study confirmed that pit and fissure sealants should be promoted strongly as an effective preventive approach for caries among community‐ or school‐based programs. Similar conditions regarding knowledge, oral hygiene practices, and attitude of school children in relation to oral health in neighboring countries, such as India, Serbia, and Iran, were observed . Thus, the results of the present study can provide useful baseline data for developing countries with similar conditions to create their own comprehensive preventive programs.…”
Section: Discussionsupporting
confidence: 66%
“…Similar conditions regarding knowledge, oral hygiene practices, and attitude of school children in relation to oral health in neighboring countries, such as India, Serbia, and Iran, were observed. [26][27][28] Thus, the results of the present study can provide useful baseline data for developing countries with similar conditions to create their own comprehensive preventive programs. With regard to future clinical research on pit and fissure sealants, all limitations in existing trials, especially in randomization, allocation concealment, and blinding, should be taken into consideration, in order to generate reliable findings and to improve the quality of clinical studies on pit and fissure sealants.…”
Section: Discussionmentioning
confidence: 99%
“…However, they visited dentist mainly when they had a specific problem. Studies have confirmed that children who practice dental visits more frequently are better informed about mouth and teeth health [20].…”
Section: Discussionmentioning
confidence: 93%
“…The result of our questionnaire suggested that children with asthma only occasionally went to dentist. Toothache was one of the main reasons for visiting dentist [20,21,22], rarely check-up or tooth restoration. These findings are consistant with results of other studies [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation